Cajal’s contributions to vestibular research - Espinosa-Sanchez, Juan M.; Perez-Fernandez, Nicolas; de Castro, Fernando; Batuecas-Caletrio, Angel (Frontiers in Neuroanatomy, 2024)
The Spanish neurohistologist Santiago Ramón y Cajal is widely regarded as the father of modern Neuroscience. In addition to identifying the individuality of cells in the nervous system (the neuron theory) or the direction followed by nerve impulses (the principle of dynamic polarization), he described numerous details regarding the organization of the different structures of the nervous system. This task was compiled in his magnum opus, "Textura del Sistema Nervioso del Hombre y los Vertebrados", first published in Spanish between 1899 and 1904, and later revised and updated in French as "Histologie du système nerveux de l'homme et des vertébrés" between 1909-1911 for wider distribution among the international scientific community. Some of Cajal´s findings are fundamental to our understanding of the anatomy and histology of the vestibular system. He depicted the nerve endings in the sensory epithelia, the structure of the vestibular nerve and Scarpa ganglion, afferent vestibular fibers, vestibular nuclei, lateral vestibulospinal tract, vestibulocerebellar connections, and the fine structure of the cerebellum. However, most of these pioneering descriptions were published years earlier in Spanish journals with limited circulation. Our study aimed to gather Cajal's findings on the vestibular system and identify his original publications. After this endeavor, we claim a place for Cajal among the founders of anatomy and histology of the vestibular system.